2022
DOI: 10.3390/brainsci12050555
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence-Guided Surgery in Glioblastoma: 5-ALA, SF or Both? Differences between Fluorescent Dyes in 99 Consecutive Cases

Abstract: Background: Glioblastoma (GBM) is the most common primary brain tumor. The extent of resection (EOR) has been claimed as one of the most important prognostic factors. Fluorescent dyes aid surgeons in detecting a tumor’s borders. 5-aminolevulinic acid (5-ALA) and sodium fluorescein (SF) are the most used. Only a few studies have directly compared these two fluorophores. Methods: A single center retrospective analysis of patients treated for GBM in the period between January 2018 and January 2021 was built to fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…A total of 937 patients were included in 10 prospective and 5 retrospective studies [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. Of 15 articles using fluorescence-guided imaging, 6 articles included lower-grade gliomas, and 13 articles included patients with GBM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 937 patients were included in 10 prospective and 5 retrospective studies [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. Of 15 articles using fluorescence-guided imaging, 6 articles included lower-grade gliomas, and 13 articles included patients with GBM.…”
Section: Resultsmentioning
confidence: 99%
“…Only one study utilized both 5-ALA and fluorescein sodium ( Table 3 C). When comparing 5-ALA and fluorescein sodium, Zeppa et al [ 50 ] included 99 patients with GBM and found no significant difference in EOR or OS between 5-ALA alone, sodium fluorescein alone, and a combined 5-ALA sodium fluorescein-guided imaging.…”
Section: Resultsmentioning
confidence: 99%
“…However, another recent meta-analysis by Smith et al [175] suggested that SF produced a 29.5% increase in GTR which was functionally equivalent to 5-ALA when compared to surgeries without fluorescent guidance. Looking forward, the combined use of both fluorophores may offer some cumulative advantages and may be the focus of future research [179].…”
Section: Fluorescencementioning
confidence: 99%
“…The same applies to various tumors of different etiologies that manifest in the human central nervous system by disturbing the intrinsic blood brain barrier (BBB) ( Mazurek et al., 2020 ; Cavallo et al., 2018 ; Schebesch et al., 2016 ; Ahrens et al., 2022 ). Some authors have even concluded that the still off-label FL dye is non-inferior to the established and approved fluorescence marker 5-aminolevulinic acid (5-ALA) with regard to the extent of resection (EOR), progression-free survival (PFS), and overall survival (OS), although these conclusions are based on different levels of evidence ( Zeppa et al., 2022 ; Naik et al., 2022 ). In a retrospective monocentric analysis, Hansen et al.…”
Section: Introductionmentioning
confidence: 99%